1976
DOI: 10.1002/macp.1976.021770118
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of (styrene‐p‐chlorostyrene) tri‐block copolymers and their properties in dilute solutions

Abstract: Two series of well-characterized (styrene-p-chlorostyrene) tri-block copolymers of B,,,A,B,-and A,B,A,-types (A : styrene monomeric unit, B: p-chlorostyrene monomeric unit. n = 2m denotes the number of units) were synthesized by anionic polymerization technique. Their intrinsic viscosities in toluene, 2-butanone, and cumene were studied over a wide range of molecular weights. The data were analyzed on the basis of two-parameter theories. The unperturbed dimensions of the block copolymers are expressed by those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1977
1977
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…4-Chlorostyrene was reported in 1976 to undergo anionic living polymerization [26]. However, it was pointed out by another research group that undesirable side reactions were observed to occur significantly between the chloride and active chain end during the anionic polymerization [27].…”
Section: Functionalized Styrene Derivatives With Less Reactive Groupsmentioning
confidence: 98%
“…4-Chlorostyrene was reported in 1976 to undergo anionic living polymerization [26]. However, it was pointed out by another research group that undesirable side reactions were observed to occur significantly between the chloride and active chain end during the anionic polymerization [27].…”
Section: Functionalized Styrene Derivatives With Less Reactive Groupsmentioning
confidence: 98%
“…Shima and co-workers reported the anionic polymerization of 1 in THF at −78 °C using oligo(styryl)disodium, followed by the sequential addition of styrene to produce the ABA triblock copolymer, polystyrene-b-poly(1)-bpolystyrene. 33 They mentioned the lower stability of the propagating carbanion derived from 1 than that of living polystyrene. Therefore, the obtained polymer contained the B homopolymer and AB diblock copolymer as impurities resulting from side reactions.…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, the anionic polymerizability of halostyrenes has not been elucidated and does not satisfy the requirement for evidence of the living anionic polymerization. , There have been several reports on the anionic polymerization behavior of halostyrenes. Shima and co-workers reported the anionic polymerization of 1 in THF at −78 °C using oligo­(styryl)­disodium, followed by the sequential addition of styrene to produce the ABA triblock copolymer, polystyrene- b -poly­( 1 )- b -polystyrene . They mentioned the lower stability of the propagating carbanion derived from 1 than that of living polystyrene.…”
Section: Introductionmentioning
confidence: 99%
“…It has been broadly investigated since 1917. Bubble growth models can be classified into two groups: single-bubble growth models [3][4][5] and cell models. [6][7][8] Zana and Leal 9 investigated the effect of the shear viscosity and surface tension on bubble collapse using a single-bubble growth model.…”
Section: Introductionmentioning
confidence: 99%